2019
DOI: 10.3390/jmse7040096
|View full text |Cite
|
Sign up to set email alerts
|

Path Analysis of Causal Factors Influencing Marine Traffic Accident via Structural Equation Numerical Modeling

Abstract: Many causal factors to marine traffic accidents (MTAs) influence each other and have associated effects. It is necessary to quantify the correlation path mode of these factors to improve accident prevention measures and their effects. In the application of human factors to accident mechanisms, the complex structural chains on causes to MTA systems were analyzed by combining the human failure analysis and classification system (HFACS) with theoretical structural equation modeling (SEM). First, the accident caus… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…However, traditional linear relationship models can no longer explain complex systems nowadays, and the SCM has been subject to criticism because simplified and linear models cannot explain the complexity, dynamics, and adaptability of the system and unexpected failures caused by system characteristics [30][31][32]. As the system thinking method can analyse the system as a whole instead of a certain part in isolation [33,34], more recently safety scientists have proposed a series of systematic thinking methods with social technology systems at the core, such as AcciMap [35], system theory accident modelling and process models (Stamp) [36], SD [37], and the functional resonance accident model (FRAM) [38].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…However, traditional linear relationship models can no longer explain complex systems nowadays, and the SCM has been subject to criticism because simplified and linear models cannot explain the complexity, dynamics, and adaptability of the system and unexpected failures caused by system characteristics [30][31][32]. As the system thinking method can analyse the system as a whole instead of a certain part in isolation [33,34], more recently safety scientists have proposed a series of systematic thinking methods with social technology systems at the core, such as AcciMap [35], system theory accident modelling and process models (Stamp) [36], SD [37], and the functional resonance accident model (FRAM) [38].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the maritime transportation industry, 80% of maritime traffic accidents (MTAs) are related to HOFs [30], such as negligence of watchkeepers, poor communication and teamwork, and lack of supervision and management. IMO revealed that human factor is one of the most important factors that lead to accidents or avoid accidents in revised guidelines for FSA [39].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The process risk is a dynamic characterization of the risk state at any time during the system's operation. It is the output of the coupling effect of uncertain (random) events under the influence of risk factors [41]. The process risk of bauxite shipping describes the development and evolution of the bauxite shipping system between the safety and accident subsystems of Handy bauxite carriers, where bauxite continuously interacts with the traffic environment over time.…”
Section: Description Of Bauxite Shippingmentioning
confidence: 99%
“…The common feature of these methods is to study the safety of complex systems from the perspective of system thinking, emphasizing the importance of interaction of multiple components in system safety analysis and standardizing the mutual constraints between systems through various constraints. Information feedback to describe the context of the system operation, just to make up for the shortcomings of traditional analysis methods, has significant advantages in dealing with system safety problems, such as software intensive, new human and organizational factors (HOF) faced by complex systems, and has attracted widespread attention in the industry [32]. Most of the existing methodologies lack inbuilt and practical techniques that take into consideration the complex interactions and dynamic feedback effects.…”
Section: Literature Reviewmentioning
confidence: 99%